Rectal Adenocarcinoma As An Uncommon Cause of Immunoglobulin A Vasculitis (Henoch-Schönlein Purpura) - Ahmet OMMA; Mehmet Emin ENECİK and Zeynep ÖZBALKAN and Sevinç CAN SANDIKÇI and Yaşar KARAASLAN (Archives of Rheumatology, 2017)
Immunoglobulin A vasculitis (Henoch-Schönlein purpura) is an immunoglobulin A-mediated vasculitis of unknown cause, which is characterized by non-thrombocytopenic purpura, arthralgia, abdominal pain, and glomerulonephritis. It most commonly occurs in children, and usually follows a benign course. It can also affect adults and is probably related to malignancy. In this article, we report a case of rectal adenocarcinoma in an immunoglobulin A vasculitis with renal involvement.